Global impact of climate change on children's health in the world - Kurniawan Taufiq Kadafi; Dimas Dwi Saputro; Martinus Martin Leman; Aslinar; Badai Buana Nasution; Dimas Tri Anantyo; Niken Wahyu Puspaningtyas; Fathy Zuandy Pohan; I Nyoman Arie Purwana; Muhammad Reza; Jaya Ariheryanto Effendy; Yogi Prawira; Piprim Basarah Yanuarso (Pediatric Sciences Journal, 2023)
Climate change has a close relationship with the greenhouse effect. The greenhouse effect is needed by the earth, but if there are too many greenhouse gases in the atmosphere this will increase the earth's temperature. Children are a group of people who have a high vulnerability to climate change. Climate change will affect children's health through 4 impacts, namely direct impacts on children's health, impacts on children's health through ecosystems, impacts on children's health through human behavior, and health impacts on children due to natural disasters. To anticipate the impact of climate change on children's health, parents and the government must take anticipatory steps so that children can be saved from the extreme dangers of climate change.